2009
DOI: 10.1002/adfm.200900026
|View full text |Cite
|
Sign up to set email alerts
|

Electroaddressing of Cell Populations by Co‐Deposition with Calcium Alginate Hydrogels

Abstract: Electroaddressing of biological components at specific device addresses is attractive because it enlists the capabilities of electronics to provide spatiotemporally controlled electrical signals. Here, the electrodeposition of calcium alginate hydrogels at specific electrode addresses is reported. The method employs the low pH generated at the anode to locally solubilize calcium ions from insoluble calcium carbonate. The solubilized Ca2+ can then bind alginate to induce this polysaccharide to undergo a localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
131
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 70 publications
2
131
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12] Among these methods, an acidic polysaccharide of sodium alginate, which can form a calcium alginate gel in the presence of calcium ions (Ca 2þ ), is widely used to entrap and immobilize prokaryotes and eukaryotic cells, such as alginate beads, [6][7][8] fibers/tubes, 9,10 and a three-dimensional (3D) cellular microarray. 11,12 Electroaddressing is an attractive technique for depositing calcium alginate gel [13][14][15] or pH-responsive chitosan 16,17 at specific addresses and in specific shapes on the preformed metal thin-film electrode surfaces that can generate protons or hydroxide ions by electrolysis on the anodes or cathodes of the electrodes. This technique is used for the assembly of cells within polysaccharide hydrogels at specific addresses with a controllable pattern.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Among these methods, an acidic polysaccharide of sodium alginate, which can form a calcium alginate gel in the presence of calcium ions (Ca 2þ ), is widely used to entrap and immobilize prokaryotes and eukaryotic cells, such as alginate beads, [6][7][8] fibers/tubes, 9,10 and a three-dimensional (3D) cellular microarray. 11,12 Electroaddressing is an attractive technique for depositing calcium alginate gel [13][14][15] or pH-responsive chitosan 16,17 at specific addresses and in specific shapes on the preformed metal thin-film electrode surfaces that can generate protons or hydroxide ions by electrolysis on the anodes or cathodes of the electrodes. This technique is used for the assembly of cells within polysaccharide hydrogels at specific addresses with a controllable pattern.…”
mentioning
confidence: 99%
“…66,67 For this application, we used the same fluid composition as above, and we prepared two batches of the fluid with red-and green-fluorescent microbeads, respectively. The microbeads are a model for a payload to be deposited at specific sites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, a biocompatible polysaccharide of sodium alginate, which can form a calcium alginate gel in the presence of calcium ions (Ca 2+ ), is widely used to entrap and immobilize prokaryotes and eukaryotic cells in 3D hydrogel structures [3][4][5]. Among these fabrication methods to form alginate hydrogels, electroaddressing is an attractive technique due to its ability to deposit alginate hydrogels [6][7][8][9][10][11][12][13] at specific addresses and in specific shapes with a controllable pattern on the preformed metal thin-film electrode surfaces. Payne et al [8,11] reported the electroaddressing of calcium alginate hydrogels, with the ability to entrap viable cell populations within the electrodeposited films.…”
Section: Introductionmentioning
confidence: 99%
“…Among these fabrication methods to form alginate hydrogels, electroaddressing is an attractive technique due to its ability to deposit alginate hydrogels [6][7][8][9][10][11][12][13] at specific addresses and in specific shapes with a controllable pattern on the preformed metal thin-film electrode surfaces. Payne et al [8,11] reported the electroaddressing of calcium alginate hydrogels, with the ability to entrap viable cell populations within the electrodeposited films. However, gel patterns involving locations, shapes and dimensions are completely subject to pre-defined configurations of microelectrodes.…”
Section: Introductionmentioning
confidence: 99%